A Self-Reconfiguration Algorithm for Sliding Triangular Modular Robots - Odem, Shlomo; Medina, Oded (IEEE robotics and automation letters, 2024)
Modular Self-Reconfigurable (MSR) robots are known for their adaptability and versatility. However, as the number of modules increases, the Self-Reconfiguration (SR) problem becomes more complex. This letter specifically addresses the SR problem in a 2D Sliding Triangular Modular Robot (STRIMOR). Our focus is on developing a mechanically simple design utilizing two module types. We also provide proof demonstrating the connectivity between any two horizontally-convex configurations. Furthermore, we propose an improved SR algorithm that eliminates the need to pass through a flat-n configuration during reconfiguration. This algorithm allows for efficient SR even in the presence of obstacles. To validate the effectiveness of our approach, we present a motion planning example featuring a STRIMOR with 1000 modules successfully navigating through a narrow gap. The contributions of this research enhance SR techniques for 2D sliding triangular modular robots, particularly those with a large number of modules. This advancement enables these robots to adapt and operate effectively in complex environments.